Critique and the Black Horizon: questioning the move 'beyond' the human/nature divide in international relations - Chipato, Farai; Chandler, David (Cambridge review of international affairs, 2024)
In the contemporary moment of the Anthropocene there appears to be a growing consensus on the need to move beyond the key modernist binary, the Human/Nature divide. We draw out a shared understanding at work in International Relations across critical approaches in Science and Technology Studies (STS), new materialist, and material feminist fields, as well as critical Indigenous, decolonial and pluriversal thought. This is an understanding that seeks to go beyond the limits of modern epistemological and ontological assumptions of human exceptionalism. These approaches seek to rework both sides of the Human/Nature divide: to reconstitute the Human as a knowing, responsive and relational subject, no longer tainted by hierarchies of race and coloniality; while, redistributing agential capacities of responsivity, care and relation beyond the Human. Drawing from work across the broad field of critical Black studies, we flag up the limitations of these entangled, relational posthuman and more-than-human imaginaries, which can easily reproduce hierarchies of subordination and control. We suggest that another approach to the Human/Nature divide is possible, a critical perspective we call the Black Horizon, focused upon the task of deconstruction: an approach which emphasises difference rather than identity, negation rather than addition, critique rather than affirmation.